Chronic Poverty and All That: The Measurement of Poverty over Time. - Calvo, C; Dercon, S (Centre for Applied Macroeconomic Analysis (Australian National University), 2007)
We explore how to measure poverty over time, by focusing on trajectories of poverty rather than poverty at a particular point in time. We consider welfare outcomes over a period in time, consisting of a number of spells. We offer a characterization of desirable properties for measuring poverty across these spells, as well as an explicit discussion of three issues. First, should there be scope for compensation so that a poor spell can be compensated for by a non-poor spell? Second, is there scope for discounting or should all spells be equally valued? Third, does the actual sequence of poor spells matter, for example whether they are consecutive or not? We offer a number of measures that implicitly offer different answers to these questions, in a world of certainty. Finally, we also offer an extension towards a forward-looking measure of vulnerability, defined as the threat of poverty over time, that incorporates risk. An application to data from Ethiopia shows that especially the assumption of compensation results in different inference on poverty.